Triple-Arterial Cannulation Approach for Whole-Body Perfusion in Infant Hypoplastic Aortic Arch and Coarctation Repair - Liebrich, Markus; Schweder, Marco; Seeburger, Joerg; Voth, Vladimir (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Organ and end-organ protection in aortic arch surgery represents a substantial challenge, especially in infants. Selective antegrade cerebral perfusion has been reported to improve organ function during this procedure. Visceral perfusion can be optimized by cannulation of the descending aorta during infant aortic arch surgery, leading to a decrease in end organ damage. However, it is associated with extensive surgical manipulation and subsequent risk of major vessel and potential organ damage. In this report, we describe a technique for distal body perfusion in an infant with hypoplastic aortic arch and isthmus stenosis by ultrasound-guided cannulation of the femoral artery using an intra-arterial vascular sheath establishing whole-body perfusion by triple cannulation.
Keywords: hypoplastic transverse aortic arch; beating heart; cerebro-myocardial perfusion; visceral perfusion